Medial prefrontal cortex-basolateral amygdala circuit dysfunction in chronic alcohol-exposed male rats. (1st March 2022) - Crofton, Elizabeth J.; Zhu, ManHua; Curtis, Katelin N.; Nolan, Gavin W.; O'Buckley, Todd K.; Morrow, A. Leslie; Herman, Melissa A.
Abstract: Alcohol is a commonly used drug that can produce alcohol use disorders (AUDs). Few individuals with AUDs receive treatment and treatment options are complicated by issues with effectiveness and compliance. Alcohol has been shown to differentially affect specific brain regions and an improved understanding of circuit-specific dysregulation caused by alcohol is warranted. Previous work has implicated both the medial prefrontal cortex (mPFC) and basolateral amygdala (BLA) in alcohol-associated plasticity, however studies directly examining the impact of alcohol exposure on this circuit are lacking. The current study employed an optogenetic strategy to investigate the prelimbic mPFC to BLA circuit and changes in circuit activity following chronic intragastric ethanol exposure in male Sprague Dawley rats. We observed monosynaptic connections with light-evoked stimulation of mPFC terminals in the BLA with efficacy and short latency. We also found that mPFC-BLA projections are primarily glutamatergic under basal inhibitory control, with a lesser population of GABAergic projections. We examined optically-evoked glutamate currents in the BLA using repeated trains of stimulation that displayed accommodation, or a reduction in evoked current amplitude over repeated stimulations. We found that following chronic ethanol exposure mPFC-BLA glutamatergic connections were dysregulated such that there were decreases in overall function, notably in synaptic strength and accommodation, with no change in probability of evoked glutamate release. The lesser GABAergic component of the mPFC-BLA circuit was not altered by chronic ethanol exposure. Collectively these data indicate that mPFC-BLA circuitry is a significant target of alcohol-associated plasticity, which may contribute to pathological behavior associated with AUDs. This article is part of the special Issue on 'Neurocircuitry Modulating Drug and Alcohol Abuse'. Highlights: Prefrontal cortex (PFC)-basolateral amygdala (BLA) circuit uses glutamate and GABA. Optogenetic PFC-BLA stimulation produces consistent accommodating evoked currents. The glutamatergic PFC-BLA circuit is regulated by basal inhibitory control. Chronic alcohol exposure decreases PFC-BLA synaptic strength and accommodation.